Sistem Seleksi Calon Siswa Bidik Misi Menggunakan Metode Simple Additive Weighting - Budi Hartanto; Bramasto Wiryawan Yudanto (STMIK Sinar Nusantara, 2021)
Vocational Senior High School of Muhammadiyah 2 Sukoharjo, opens Student Scholarship of Bidik Misi to accept new students in every admission period of academic year. This school has difficulty to decide the candidates of scholarship grantee. In this research, there is solution by creating selection system to select the candidate of scholarship grantee using Simple Additive Weighting method. This research uses parents’ income, family living cost, students’ grades, and students’ achievement. This research also uses a Usecase Diagram to design the system. To test the system, this research uses Blackbox testing method. There are 25 valid questions in research result so that this application is suitable to select the new students. Based in its result, additive simple weighting method can be used as a method to support decision, especially in the selection of scholarship grantee candidates.